2021
DOI: 10.1016/j.ijid.2021.02.089
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with a prolonged negative conversion of viral RNA in patients with COVID-19

Abstract: Objectives Our study aimed to identify the factors influencing the delay in SARS-CoV-2 RNA negative conversion. Methods A cohort study including COVID-19 patients admitted to the Tunisian national containment center was conducted. The follow-up consisted of a weekly RT-PCR test. Multivariate Cox regression analysis was performed to determine independent predictors associated to negative RNA conversion. Results Among 264 patients included, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 21 publications
6
26
1
Order By: Relevance
“…However, there was no significant relationship between preexisting diabetes or hypertension and the classification of COVID-19. Consistent with the study from Bennasrallah et al, diabetes and hypertension could not act as predisposing factors for late SARS-CoV-2 viral clearance [ 11 ]. In addition, T2DM was not significantly related to prolonged viral RNA conversion time or the proportion of RPV ( P > 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…However, there was no significant relationship between preexisting diabetes or hypertension and the classification of COVID-19. Consistent with the study from Bennasrallah et al, diabetes and hypertension could not act as predisposing factors for late SARS-CoV-2 viral clearance [ 11 ]. In addition, T2DM was not significantly related to prolonged viral RNA conversion time or the proportion of RPV ( P > 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…1 ). Several other studies have also revealed the presence of fever was significantly associated with prolonged DoVC ( Zhou et al, 2021 ; Bennasrallah et al, 2021 ). These patients were hypothesized to be more severely affected by the SARS-CoV-2 infection in the lungs and thus the prolonged DoVC ( Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 72%
“…18 Vulnerabilities to contagions are especially related to the level and duration of exposure. 19 The longer a person is exposed to a source of infection, the higher the likelihood of being infected. Traditional gender roles attributed to different gender strata in Africa demand men to work outdoors and secure resources for the family while women stay at home.…”
Section: Discussion and Implications For Translationmentioning
confidence: 99%